Structure making and breaking in electrolyte solutions explained by water energetics - Lucia F. Sedano; Luis Carlos Pardo; Gustavo Madrigal; Eva G. Noya; Carlos Vega (Proceedings of the National Academy of Sciences, 2026)
The long-standing classification of ions as water “structure-makers” or “structure-breakers” is fundamentally reevaluated through advanced Molecular Dynamics simulations employing the accurate Madrid-2019 force field. We quantitatively study the local hydration structures of 1 m aqueous solutions of LiCl, NaCl, and KCl (through local entropy and Kullback-Leibler (KL)-divergence analysis). We demonstrate that all ions act as net disruptors of water’s tetrahedral network, this change being more severe in solutions with high charge density ions. While hydrogen bonding (HB) is diminished within the first hydration shell (FHS) of ions, it returns to bulk-like levels beyond it. From an energetic viewpoint, water–water interactions in solution are destabilized by about 15% compared to pure water, confirming all ions as “structure-breakers” in this regard. Two factors contribute to the energy loss of water: Roughly half arises from a 5% reduction in the total number of HBs, localized primarily within the ions’ hydration shells (plus a small contribution from HB distortion); whereas the other half originates from the destabilization of dipole–dipole correlations beyond the FHS. This latter effect, which scales with ionic charge density, is absent for uncharged solutes. Finally, we identify a correlation between the total energy of water (including the ion–water contribution) in solution and the Jones-Dole B coefficient—a correlation that also holds for divalent cations and hydrophobic solutes. The transition from “structure-maker” to “structure-breaker” (i.e., the change of sign in the B coefficient) occurs near the locus where the total energy of water in the solution is similar to that of pure water.